Dislocation Of Shoulder Joint - Hafizuddin, AH Ahmed (KYAMC Journal, 2013)
Dislocation means complete loss of contact of the articular surfaces of bony components of a joint. Shoulder joint is the most commonly dislocated large joint. Dislocation of shoulder joint has been recognized for centuries as an injury in both young and old. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13519 KYAMC Journal Vol.2(1) 2011 pp.140-144